1993
DOI: 10.1017/s0016672300031207
|View full text |Cite
|
Sign up to set email alerts
|

The role of growth hormone in lines of mice divergently selected on body weight

Abstract: An understanding of the physiological and genetic changes which determine the response to selection is critical for both evolutionary theory and to assess the application of new molecular techniques to commercial animal breeding. We investigated an aspect of physiology, growth hormone (GH) metabolism, which might a priori have been expected to play a large part in the response of mouse lines selected for high or low body weight. Disruption of endogenous GH or addition of exogenous GH had similar proportionate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…These data together suggest that fast-growing strains may already have up-regulated GH and/or its downstream pathways such that further stimulation with this hormone is dampened relative to unselected strains. In mice, although effects of GH protein treatment were found to be similar in fast-growing and slowgrowing strains (39), GH transgenesis had a greater effect in slow-growing strains (40,41). Collectively, these phenotypic data suggest that domestication in vertebrates may be using the same genetic and physiological pathways regulated by the GH endocrine axis.…”
Section: Discussionmentioning
confidence: 84%
“…These data together suggest that fast-growing strains may already have up-regulated GH and/or its downstream pathways such that further stimulation with this hormone is dampened relative to unselected strains. In mice, although effects of GH protein treatment were found to be similar in fast-growing and slowgrowing strains (39), GH transgenesis had a greater effect in slow-growing strains (40,41). Collectively, these phenotypic data suggest that domestication in vertebrates may be using the same genetic and physiological pathways regulated by the GH endocrine axis.…”
Section: Discussionmentioning
confidence: 84%
“…In particular, elevated GH transcription rates might account for the accelerated growth with high protein accretion in the selected lines. 26 For transgenic mice overexpressing GH, it has been demonstrated that accelerated growth is not induced until the age of three weeks. 27 Increased GH levels being the main modulator of IGF-1 transcription 28 is probably the reason for the observed elevation of the IGF-1 serum concentrations in both selected lines, compared to the control group, at the age of three weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In previous experiments on our body weight lines, growth of lit\lit homozygotes on a high line background was more depressed than growth of the low selected lines in absolute terms, but was of similar proportion (Hastings et al, 1993). In a later study (Bu$ nger et al, 1998 b), significant differences were also found on the log scale, but they were relatively small.…”
Section: Introductionmentioning
confidence: 53%
“…In a later study (Bu$ nger et al, 1998 b), significant differences were also found on the log scale, but they were relatively small. Further, exogenous GH administration to wild-type and to lit\lit mice gave similar proportionate responses in weight gain in the high and low lines but much larger absolute responses in the lit\lit animals (Hastings et al, 1993). A significant effect of the lit gene on fatness and a higher increase of fatness in the high than in the low body weight line were found.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation